HIV, Cancer, and the Microbiota: Common Pathways Influencing Different Diseases - Herrera, Sabina; Martínez-Sanz, Javier; Serrano-Villar, Sergio (Frontiers in Immunology, 2019)
HIV infection exerts profound and perhaps irreversible damage to the gut mucosal-associated lymphoid tissues, resulting in long-lasting changes in the signals required for the coordination of commensal colonization and in perturbations at the compositional and functional level of the gut microbiota. These abnormalities in gut microbial communities appear to affect clinical outcomes, including T-cell recovery, vaccine responses, HIV transmission, cardiovascular disease, and cancer pathogenesis. For example, the microbial signature associated with HIV infection has been shown to induce tryptophan catabolism, affect the butyrate synthesis pathway, impair anti-tumoral immunity and affect oxidative stress, which have also been linked to the pathogenesis of cancer. Furthermore, some of the taxa that are depleted in subjects with HIV have proved to modulate the anti-tumor efficacy of various chemotherapies and immunotherapeutic agents. The aim of this work is to provide a broad overview of recent advances in our knowledge of how HIV might affect the microbiota, with a focus on the pathways shared with cancer pathogenesis.